The The Riau Islands Province Arts Building in Tanjungpinang City - Fajar Noer Kholis (Institut Seni Indonesia Denpasar, 2023)
The activities of art actors in Tanjungpinang City are not well developed because they are not supported by the existence of supporting art activity facilities. This study aims to plan and design the Riau Islands Province Arts Building in Tanjungpinang which can accommodate various forms of art in it. The theme